Theoretical Foundation for Mechanical Products Service Life Prediction; IOP Conference Series: Materials Science and Engineering; Vol. 125 : Materials Treatment: Current Problems and Solutions - Konovodov V. V.; Valentov A. V. Aleksandr Viktorovich; Lafetova T. V.; Basalaev M. N. (2016, 2016)
Title screen